1975
DOI: 10.1103/revmodphys.47.s1
|View full text |Cite|
|
Sign up to set email alerts
|

Report to the American Physical Society by the study group on light-water reactor safety

Abstract: The issue of light-water reactor (LWR) safety has been the subject of a part-time, year-long study sponsored by the American Physical Society. The goal of the study was the assessment of some of the technical aspects of the safety of large light-water nuclear power reactors typical of present commercial practice in the Unted States. The report examines issues related to safe operation of LWRs; the research and development program responsible for establishing and enhancing safety; and the consequences of accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…After substantial analysis by the Soviets (45) and others (46, 47), the Chernobyl sourc e term was shown to be similar to the "worst-case" hypotheti cal pressurized water reactor accident, PWR-2, described in the US PRA literature (50). As shown in Figure 4, the Soviet release was equal to PWR-2 for the more volatile radionuclides, and exceeded PWR-2 for the least vola tile.…”
Section: Three Mile Island and Chernobylmentioning
confidence: 77%
“…After substantial analysis by the Soviets (45) and others (46, 47), the Chernobyl sourc e term was shown to be similar to the "worst-case" hypotheti cal pressurized water reactor accident, PWR-2, described in the US PRA literature (50). As shown in Figure 4, the Soviet release was equal to PWR-2 for the more volatile radionuclides, and exceeded PWR-2 for the least vola tile.…”
Section: Three Mile Island and Chernobylmentioning
confidence: 77%
“…For instance, PRA has been fiercely controversial from its beginning, as epitomized by a dispute around the WASH-1400 report. 68 Until gradually developing a concept of RIDM in which the PRA results would be prudently incorporated in safety decisions, the discussion around PRA has taken a detour, such as an ambitiously technocratic concept of risk-based decision making. 69 There are still a number of debates over how to implement the RIDM concept even in the United States, which has a long history of PRA and safety goals.…”
Section: Va Deep Structural Roots Of Ignorancementioning
confidence: 99%
“…However, rather than resolving the question of nuclear safety, it sparked intense controversy. Reviews from the American Physical Society and the Nuclear Regulatory Commission, examining the scientific judgments underlying WASH-1400 (19,20), concluded that there was no reason to believe that the report's risk estimates were biased upward or downward. However, the reviewers were confident that those estimates had been stated with unwarranted certainty.…”
Section: Analyzing Risks From One Source: Nuclear Powermentioning
confidence: 99%